2002
DOI: 10.1080/14756360290005598
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Schiff Bases of Oxalyl-hydrazine/diamide Incorporating Pyrrolyl and Salicylyl Moieties and of Their Zinc(II) Complexes

Abstract: Schiff bases derived from oxaldiamide/oxalylhydrazine and pyrrol-2-carbaldehyde, or salicylaldehyde respectively, as well as their Zn(II) complexes have been prepared and tested as antibacterial agents. These Schiff bases function as tetradentate ligands, forming octahedral Zn(II) complexes. The ketonic form for the diamide derived Schiff base and the enolic form of the hydrazide derived Schiff base were the preferred tautomers for coordination of the metal ions. The title compounds and their Zn(II) derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 12 publications
2
32
0
Order By: Relevance
“…The separated solid was filtered, washed with water and recrystallized from ethanol. Cl)-, C-4"), 146.47 (C-8a), 154.00 (C-2), 159.22 (C-4), 164.40 (H-C=N) 13 …”
Section: General Methods For the Preparation Of 3a-jmentioning
confidence: 99%
See 2 more Smart Citations
“…The separated solid was filtered, washed with water and recrystallized from ethanol. Cl)-, C-4"), 146.47 (C-8a), 154.00 (C-2), 159.22 (C-4), 164.40 (H-C=N) 13 …”
Section: General Methods For the Preparation Of 3a-jmentioning
confidence: 99%
“…After proper assignment of the entire proton spectrum, the proton carbon correlation spectrum was further analyzed to assign the eleven 13 C-H peaks. The quaternary carbon peaks were assigned intuitively with the help of 13 C-NMR spectra.…”
Section: Interpretation Of Spectral Datamentioning
confidence: 99%
See 1 more Smart Citation
“…A heterocyclic ligand with multifunctionality has a greater chance of interaction either with nucleoside bases or with biologically essential metal ions present in the biosystem and can be promising candidates as bactericides since they always tend to interact especially with some enzymatic functional groups, in order to achieve higher coordination numbers [23,24]. Moreover, enhancement in antibacterial activity on coordination with metal ion is probably due to the presence of donor systems in the uncoordinated compound or the coordinately unsaturated species formed may inhibit enzyme production since the enzymes which require these groups for their activity, appear to be more susceptible to deactivation upon coordination [25]. Thus antibacterial property of metal complexes cannot be ascribed to chelation alone but it is an intricate blend of all the above contributions.…”
Section: Antibacterial Screeningmentioning
confidence: 99%
“…The plates were incubated immediately at 378C for 20 h. Activity was determined by measuring the diameter of zones showing complete inhibition (mm). Growth inhibition was compared [19] with the standard drug (Tables II & III). In order to clarify any participating role of DMF in the biological screening, separate studies were carried out with the solutions alone of DMF and they showed no activity against any bacterial strains.…”
Section: Preparation Of Copper (Ii) Complexe With Lmentioning
confidence: 99%